Thermal, Mechanical, and Photophysical Properties of Carbazole-Substituted POSS and Ladder Polysilsesquioxane - Lee, Albert S.; Jo, Young Yeol; Choi, Seung-Sock; Baek, Kyung-Youl; Hwang, Seung Sang (AMER SCIENTIFIC PUBLISHERS, 2017)
Through UV-initiated thiol-ene click chemistry, carbazole-substituted ladder-like structured polysilsesquioxane and cage-structured polyhedral oligomeric silsesquioxane (T8-POSS) compounds were synthesized and fully characterized. Perfectly carbazole-substituted T8-POSS was synthesized via post-modifications of a mercaptopropyl T8-POSS, while the ladder polysilsesquioxane was synthesized through a base-catalyzed hydrolysis-polycondensation reaction with a carbazole-substituted trialkoxysilane monomer. Through a comparative evaluation of the thermal, mechanical, and photophysical properties of the synthesized compounds, we demonstrate the utility and superiority of the ladder-like structure over the T8-POSS material.
Keywords: POLYHEDRAL OLIGOMERIC SILSESQUIOXANE; THERMOPLASTIC POLYSILSESQUIOXANES; STRUCTURED POLYSILSESQUIOXANE; DEVICES